Manajemen Penanggulangan Bencana Banjir, Puting Beliung, dan Tanah Longsor di Kabupaten Jombang - Farichatun Nisa (JKMP (Jurnal Kebijakan dan Manajemen Publik), 2014)
The purpose of this study to analyze and describe the disaster management by Regional Disaster Management Agency (BPBD) and communnity participation in disaster management in Jombang Regency. This study used a qualitative approach with descriptive method. The selection of informant’s used purposive sampling technique. The results of this research showed that the disaster management conducted by Regional Disaster Management Agency (BPBD) through the stages of response, recovery, and development. The most dominant stages are performed by response on actions before and after the disaster. Meanwhile, disaster management by the community is performed by participation in the form of manpower, energy, skill, and material, as well as social participation. Dominant participation from community was manpower participation and social participation.